The Interactions of Cultural and Climatic Influences in Architectural Forms in Historical Qajar Houses in "Cold" and "Hot and Dry" Climates - Mohammed Reza Namdari; Ali Mash’hadi; Aila Sinai (صفه)
The physicality of historical houses in Iran have always been affected by various factors of their context, e.g., cultural factors, religious beliefs, rituals, religious approaches, social security and climate comfort, all of which affecting the quality of indoor spaces and formal characteristics in various ways. The orientation of the house, materials and consumables, decorations, hierarchy, geometry, scale, light and illumination are among these characteristics. This paper compares and evaluates the influence of cultural and climatic factors on the architecture of historical houses of the Qajar era in the cold-mountainous and hot-dry climates of Iran. The research method is descriptive-analytical-comparative, through library and field studies. To do so, four Qajar houses with central courtyard and block forms were selected in the key cities of the above climates to compare their contrasting forms, and the way physical and spatial components are affected by different factors. The comparison shows that the form, hierarchies, orientation and use of natural materials are among the indicators influenced by cultural factors in both climates. In the hot and dry climate, the cultural factor most effective on the scale of the house and the functions of the spaces, with materials, compositions, façade and ornaments having also benefited from the climate, while in the cold and mountainous climate, the scale and function having fruitfully been affected from the climate.